HISTOPATHOLOGY OF GILL AND BRAIN OF TILAPIA (Oreochromis niloticus) THAT WERE INFECTED WITH Streptococcus iniae - Marwati '; Morina Riauwaty Siagian; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on July until Desember 2015 at Parasite and Fish Disease Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The aims of this research was to determine a gill and brain tissue changes of Tilapia (O. niloticus) infected by S. iniae with different concentration. This research used experimental method, infected with according to treatment and were analyzed. The treatments applied were intraperitoneal infection by S. iniae with different concentration, they were ; Kn (negative control, were not infected by S. iniae), P1 (infection by S. iniae with concentration 109 CFU/mL), P2 (infected by S. iniae with concentration 107 CFU/mL), P3 (infected by S. iniae with concentration 105 CFU/mL), and than fishes were reared for 7 days. Gill tissue showed hyperplasia, fusion in lamella and haemorrhage, gill tissue condition in P1 and P2 suffered in the same destruction with moderate category, and gill tissue condition in P3 in light category. The brain tissue showed haemorrhage, congestion and necrosis. Damage to the gill and brain tissue of tilapia due to S. iniae infected.Key words : Oreochromis niloticus, Streptococcus iniae, Histopathology, Gill and Brain